Exploring the Influencing Factors of Teachers' Beliefs toward the Use of Multiple Intelligences based English Teaching - Faidah, Ririn Tutik; Fauziati, Endang; suparno, suparno (Advances in Social Sciences Research Journal, 2019)
Abstract Teacher beliefs become an important part of the teachers in the instruction process. In shaping their beliefs, teachers are influencing by many aspects around them. Those aspects are considered essential in shaping the teachers beliefs on how to act in the classroom practice. This study aims to find out the contributing factors in shaping the primary teachers beliefs toward the use of multiple intelligences based English teaching. The participants of this study were two primary English teachers who have been teaching with multiple intelligences based instruction for more than 3 years in a private primary school which run multiple intelligences system. The results showed that there are two main factors shape the teachers’ beliefs on multiple intelligences based English teaching. Those main factors were the internal factors and the external factors. Those factors give important contribution in shaping the teachers beliefs when implements the multiple intelligences based English teaching in the classroom practice.